(3Gdbhd aj MLjI GdXf hYOegGs - (3eLghds
(3ChdgG (B:s
(3OQS aj MLjI GdNHQ GdhMO GdYGQj Yf GdbQGFf GdeajOI ddbWY(B...s
(3BNQgG (B:s
(3GdOdjdGf GdeYJHQGf GdeJNGdaGf (B... (3de jQLYhG Edi GdCUd Hjf Mceges
(3JHUQI GdYfhGf (B:s
(3QSGdI aj MLjI GdNHQs
(3JHUQI GdeDda (B:s
(3dYdg GdLRA GdKGfj Ch GdKGdK ef cJGH(B: (3cTa GdCUhd aj CUhd Gdabg, dCHj GdbGSe Hf eMeO UGOb GdfhQGFj GdSOgj, GdeJhaj (B1305(3g`(B. (3GfXQ GdPQjYI Qbe(B: 472(3, (B18/15s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs